Comparative genomics of closely related Salmonella enterica serovar Typhi strains reveals genome dynamics and the acquisition of novel pathogenic elements - Yap, Kien-Pong (BMC Genomics, 2014)
BACKGROUND: Typhoid fever is an infectious disease of global importance that is caused by Salmonella enterica subsp. enterica serovar Typhi (S. Typhi). This disease causes an estimated 200,000 deaths per year and remains a serious global health threat. S. Typhi is strictly a human pathogen, and some recovered individuals become long-term carriers who continue to shed the bacteria in their faeces, thus becoming main reservoirs of infection. RESULTS: A comparative genomics analysis combined with a phylogenomic analysis revealed that the strains from the outbreak and carrier were closely related with microvariations and possibly derived from a common ancestor. Additionally, the comparative genomics analysis with all of the other completely sequenced S. Typhi genomes revealed that strains BL196 and CR0044 exhibit unusual genomic variations despite S. Typhi being generally regarded as highly clonal. The two genomes shared distinct chromosomal architectures and uncommon genome features; notably, the presence of a ~10 kb novel genomic island containing uncharacterised virulence-related genes, and zot in particular. Variations were also detected in the T6SS system and genes that were related to SPI-10, insertion sequences, CRISPRs and nsSNPs among the studied genomes. Interestingly, the carrier strain CR0044 harboured far more genetic polymorphisms (83% mutant nsSNPs) compared with the closely related BL196 outbreak strain. Notably, the two highly related virulence-determinant genes, rpoS and tviE, were mutated in strains BL196 and CR0044, respectively, which revealed that the mutation in rpoS is stabilising, while that in tviE is destabilising. These microvariations provide novel insight into the optimisation of genes by the pathogens. However, the sporadic strain was found to be far more conserved compared with the others. CONCLUSIONS: The uncommon genomic variations in the two closely related BL196 and CR0044 strains suggests that S. Typhi is more diverse than previously thought. Our study has demonstrated that the pathogen is continually acquiring new genes through horizontal gene transfer in the process of host adaptation, providing novel insight into its unusual genomic dynamics. The understanding of these strains and virulence factors, and particularly the strain that is associated with the large outbreak and the less studied asymptomatic Typhi carrier in the population, will have important impact on disease control. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2164-15-1007) contains supplementary material, which is available to authorized users.